Engagement of Toll‐like receptor 2 enhances interleukin (IL)‐17+ autoreactive T cell responses via p38 mitogen‐activated protein kinase signalling in dendritic cells. (November 2014) - Wei, R.; Dong, L.; Xiao, Q.; Sun, D.; Li, X.; Nian, H.
Summary Functional analysis of single Toll‐like receptors (TLRs) in vivo is necessary to understand how they shape the ocular inflammation involved in uveitis. In this study we explored the role and mechanisms of TLR‐2 agonists on the autoreactive T helper type 17 (Th17) response in experimental autoimmune uveitis (EAU). Treatment by peptidoglycan (PGN), a specific TLR‐2 agonist, remarkably increased mRNA levels of Th17‐lineage genes interleukin (IL)‐17A, IL‐21 and RAR‐related orphan receptor (ROR)γt and promoted antigen‐specific Th17 response in EAU mice. A mixture of PGN and interphotoreceptor retinoid‐binding protein peptide (IRBP161–180) could effectively induce EAU in the absence of complete Freund's adjuvant (CFA). PGN treatment also enhanced the pathogenic activities of activated antigen‐specific Th17 cells in vivo. PGN significantly increased the production of IL‐1β, IL‐6 and IL‐23 of dendritic cells (DCs) and enhanced their ability to promote IL‐17+ uveitogenic T cells. Enhanced immunostimulatory activities of PGN‐DCs depend upon p38 activation. Inhibition of p38 mitogen‐activated protein kinase (MAPK) activity dramatically decreased IL‐17 gene expression and antigen‐specific Th17 responses stimulated by PGN‐DCs. Our findings suggest that PGN treatment dramatically promotes the IL‐17+ uveitogenic T cell responses via enhancing the immunostimulatory activities of DCs. This effect may be mediated, at least in part, by activation of the p38 signalling pathway in DCs.